PENGARUH BERBAGAI PH SARI BUAH DAN SUHU PASTEURISASI TERHADAP AKTIVITAS ANTIOKSIDAN DAN TINGKAT PENERIMAAN SARI KULIT BUAH MANGGIS - Gupita, Claudia Norma; Rahayuni, Arintina (Journal of Nutrition College, 2012)
ABSTRACTBackground: Oxidative stress is associated with the progression of degenerative disease. The consumption of antioxidant resources to prevent the body from oxidative stress damage. Mangosteen fruit hull is one of the mangosteen waste which has potential activity of natural antioxidant, such as xanthone and anthocyanins. Xanthon and anthocyanins influenced by pH and heating. Therefore, it is necessary to study about the effect of pH and temperature pasteurized on antioxidant activity of the mangosteen fruit hull juice.Objective : Analyze the effect of antioxidant activity and the level of acceptance of the mangosteen fruit hull juice with various pH and pasteurization temperature. Methods : An experimental study with a factorial design which combines pH (pH 3 and pH 4) and pasteurization temperature (temperature of 750C, 850C, 950C). The analyzes are antioxidant activities and the level of acceptance. The antioxidant activity obtained with DPPH (2,2 dhipenyl -1-pycrilhidrazyil) test. The acceptance test are conducted with hedonic test. Statistical analysis of the antioxidant activity using Two Way ANOVA test CI 95%, while the level of acceptance using Friedman test followed Wilcoxon test. Result : The result of antioxidant activity of mangosteen fruit hull juice ranged 80.64-89.70%. The various pH and pasteurization temperature did not effect the antioxidant activity of the mangosteen fruit hull juice. The results ofÂ  test acceptance, color and taste are affected by variations in pH and temperature pasteurization, except aroma. The more acidic pH of juice, mangosteen fruit hull juice color of the panelists preferred. Acidification can not relieve harsh flavor mangosteen fruit hull juice. All mangosteen fruit hull juice aroma panelists preferred.Conclucion : The various pH and pasteurization temperature did not effect the antioxidant activity of the mangosteen fruit hull juice. The results ofÂ  test acceptance, color and taste are affected by variations in pH and temperature pasteurization, except aroma. Keyword : antioxidant activity, mangosteen fruit hull juice, pH, pasteurization temperature